Initial respiratory specimen bacteriology and isolates susceptibility to antimicrobials in promptly intubated chronic obstructive pulmonary disease adults - single-center two-year experience - Gluvić Zoran; Mitrović Bojan; Radojević Biljana; Krasnjuk Andrej; Panić Miloš; Miličević Predrag; Vukčević Miodrag; Tomašević Ratko; Putniković Biljana; Nešković Aleksandar N. (Srpski Arhiv za Celokupno Lekarstvo, 2019)
Introduction/Objective. Chronic obstructive pulmonary disease (COPD) exacerbation is mostly triggered by infectious agents and seriously compromises the patient’s quality of life and predicts a poor outcome of the disease as well. If the signs of the probable bacterial cause of COPD exacerbation are presented in an intubated patient, initial antimicrobial management must be launched. Depending on the results of the respiratory system sample cultures, the initial antimicrobials can be changed or continued. The objective of this study is to present in-hospital suggestions regarding the use of the initial antimicrobial management of urgently intubated COPD adults with the probable bacterial cause of exacerbations, considering the source of bacterial acquisition (i.e. facility- or community-acquired bacteria). Methods. The cross-sectional study covered 51 patients urgently intubated on admission to the medical Intensive Care Unit of the Zemun Clinical Hospital Center during 2015/2016. The patients were divided into two groups: community-acquired (n = 26) and facility-acquired infection group (n = 25). The respiratory system samples were processed in the Microbiology Laboratory. Results. Acinetobacter and Pseudomonas spp. were the most frequently isolated bacteria in both groups, followed by Staphylococcus aureus and Klebsiella spp. as the third most frequent bacteria in the community- and facility-acquired group, respectively. The parallel use of tigecycline and aminoglycosides proved to cover a sensitive microbial spectrum in 52% of examinees of the community-acquired and 32% of examinees of the facility-acquired group. Conclusion. The present study suggests the initial management of intubated adults with probable bacterial infection-induced COPD exacerbation by the parallel use of tigecycline and aminoglycosides. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 173033]